Spontaneous Carotid-Cavernous Fistula and Subarachnoid Hemorrhage - Damelan Kombate; Kokou Mensah Guinhouya; kossivi kumako vinyo Apetse; mofou Belo; agnon ayélola koffi Balogou (Journal of Neurological Research And Therapy, 2016)
Carotid-cavernous fistula (CCF) is a rare neurological condition with risk of death in case of inappropriate management. The outcome of this pathology is very bad in developing countries with inadequate technical Platform. We underlined the main difficulties of the management of CCF in a 43 years-old Togolese woman with a fatal outcome.
Keywords: carotid-cavernous fistula